A survey on total parenteral nutrition in 55, 000 hospitalized patients: Retrospective cohort study using a medical claims database. (October 2020) - Sasabuchi, Yusuke; Ono, Sachiko; Kamoshita, Satoru; Tsuda, Tomoe; Murano, Haruka; Kuroda, Akiyoshi
Summary: Background & aims: Identifying the prevalence of underfed patients and risk factors for underfeeding in patients with total parenteral nutrition (TPN) is essential to improve the management of patients receiving TPN. The aim of this study was to examine the prevalence and risk factors for underfeeding using a medical claims database. Methods: In this retrospective cohort study using a medical claims database, we analyzed patient characteristics, timing and duration of nutrition prescription, daily dose of nutrients, and types of parenteral nutrition products administered after central venous catheter (CVC) insertion in hospitalized Japanese patients between 2009 and 2018. The mean prescriptions of energy <20 kcal/kg/day, amino acids <1.0 g/kg/day, and fat <2.5 g/day received by patients between the 4th and 10th day after CVC insertion were regarded as underfeeding. To study the association between nutritional adequacy and body mass index (BMI) with TPN, the proportions of patients with a prescription of energy ≥20 kcal/kg/day or amino acids ≥1.0 g/kg/day were calculated and categorized according to BMI, and the Cochran-Armitage trend test was performed. Results: Of 54, 687 patients included in the study, 70.3% were aged ≥70 years, and 31.3% had a BMI <18.5. The mean prescription of energy was insufficient in 49.9% of patients, and 82.9% were insufficiently prescribed with amino acids. In addition, 44.4% of the patients were never prescribed a single dose of fat emulsion during their hospital stay. On the 10th day after CVC insertion, the majority of patients used commercial 2-in-1 compounds containing carbohydrates and amino acids. A higher BMI was associated with underfeeding of energy and amino acids (both p < 0.001). Conclusions: It is important to adjust the nutrition dose according to the patient's body size and weight, and it is necessary to supplement inadequate nutrients by single-nutrition solutions in addition to compounded solutions.